The first experience with brolucizumab for neovascular age-related macular degeneration - A.N. Kulikov; D.S. Maltsev; A.Yu. Malafeeva; S.M. Perminova; V.R. Zhalimova; A.S. Vasiliev; A.A. Kazak (РМЖ "Клиническая офтальмология")
A.N. Kulikov, D.S. Maltsev, A.Yu. Malafeeva, S.M. Perminova, V.R. Zhalimova, A.S. Vasiliev, A.A. Kazak S.M. Kirov Military Medical Academy, St. Petersburg, Russian Federation Aim: to assess the efficacy and safety of brolucizumab in Russian patients with neovascular age-related macular degeneration (nAMD). Patients and Methods: this study enrolled 47 patients with nAMD divided into two groups. Group 1 included 13 treatment-naïve patients/13 eyes (12 men and 1 woman, mean age 72.4±9.5 years, mean best-corrected visual acuity (BCVA) 0.43±0.32). Group 2 included 34  patients having active nAMD despite ongoing treatment/34 eyes (25 men and 9 women, mean age 74.1±8.0 years, mean BCVA 0.46±0.25). All patients received at least two intravitreal injections of brolucizumab (in total, 137 injections) with a 1-month interval. Patients were examined one month after the 2nd injections. BCVA, central macular thickness (CMT), macular volume (MV), sub/intraretinal fluid, and adverse events were evaluated. Results: in group 1, a significant increase in BCVA from 34.9±6.6 letters to 44.1±4.2 letters (p=0.02) was reported. Meanwhile, in group 2, BCVA remained unchanged (35.0±3.5 letters before treatment vs. 33.8±3.7 letters after treatment, p>0.05). In group 1, CMT and MV significantly reduced, while in group 2, only MV significantly reduced (p<0.05). A significant reduction in the cumulative rate of sub/intraretinal fluid was detected in both groups (p<0.05). Conclusions: treatment-naïve patients who received brolucizumab demonstrated a significant improvement of anatomical and functional parameters. Meanwhile, patients with active nAMD despite ongoing treatment who received brolucizumab demonstrated a significant reduction in disease activity and tendency to the improvement of anatomical (but not functional) parameters. Keywords: age-related macular degeneration, brolucizumab, optical coherence tomography, anti-VEGF therapy. For citation: Kulikov A.N., Maltsev D.S., Malafeeva A.Yu. et al. The first experience with brolucizumab for neovascular age-related macular degeneration. Russian Journal of Clinical Ophthalmology. 2022;22(2):108–115 (in Russ.). DOI: 10.32364/2311-7729-2022-22-2-108-115.